Unicystic ameloblastoma marsupialization treatment: A case report - Eddin, Sana S.; Aljareh, Abeer; Al-Saleh, Walid; Eddin, Mohammad C. (Hasanuddin University, 2024)
Unicystic ameloblastoma is rare and the least aggressive type of ameloblastoma tumor, it comprises 6% of all ameloblastoma types and more frequently affects the mandibular jaw.The clinical case reports a 21-years-old male who had a mandibular swelling at the right retromolar region. Panoramic radiograph and CBCT images revealed an unicystic radiolucency and sizing 2.0×1.5 cm. A provisional differential diagnosis of unicystic ameloblastoma was considered. The treatment steps were: conservative marsupialization treatment, monthly follow-up until cystic volume shrinkage, a complete cystic remnants removal by a bone curettage after 10 months, and an every 6-months follow-up including clinical and image examination. There was none sign of recurrence after 5 years of follow-up.